Paricalcitol versus cinacalcet plus low-dose vitamin D for the treatment of secondary hyperparathyroidism in patients receiving haemodialysis: study design and baseline characteristics of the IMPACT SHPT study - Ketteler, M.; Martin, K. J.; Cozzolino, M.; Goldsmith, D.; Sharma, A.; Khan, S.; Dumas, E.; Amdahl, M.; Marx, S.; Audhya, P. (Nephrology, dialysis, transplantation, 2012)
Paricalcitol and cinacalcet are common therapies for patients on haemodialysis with secondary hyperparathyroidism (SHPT). We conducted a multi-centre study in 12 countries to compare the safety and efficacy of paricalcitol and cinacalcet for the treatment of SHPT. Patients aged ≥18 years with Stage 5 chronic kidney disease receiving maintenance haemodialysis and with intact parathyroid hormone (iPTH) 300-800 pg/mL, calcium 8.4-10.0 mg/dL (2.09-2.49 mmol/L) and phosphorus ≤6.5 mg/dL (2.09 mmol/L) were randomized within two strata defined by the mode of paricalcitol administration to treatment with paricalcitol- (intra-venous, US and Russian sites, IV stratum; oral, non-US and non-Russian sites, oral stratum) or cinacalcet-centred therapy. The primary endpoint is the proportion of patients in each treatment group who achieve a mean iPTH value of 150-300 pg/mL during Weeks 21-28 of treatment. Assuming efficacy response rates of 36 and 66% for cinacalcet and paricalcitol, respectively, and a 20% discontinuation rate, 124 subjects in each stratum were estimated to provide 81% power to detect a 30% absolute difference in the primary endpoint. Of 746 patients screened, 272 (mean age, 63 years; mean iPTH, 509 pg/mL) were randomized. Mean duration of haemodialysis at baseline was 3.7 years. Comorbidities included hypertension (90.4%), Type 2 diabetes (40.4%), congestive heart failure (17.3%), coronary artery disease (34.6%) and gastrointestinal disorders (75%). The study participants are representative of a multinational cohort of patients on haemodialysis with elevated iPTH. The study results will provide valuable information on the best available treatment of SHPT in patients on haemodialysis.